Improving Students’ Achievement In Descriptive Text Through the Application (STAD) Student Team Achievement Division - Sardi; Edi Suprayetno (Journal of Classroom Action Research, 2022)
Language learning is very important for human’s social development. As a language which is used by more than a half of population in the world, English hold the key as international language. English is a tool of communication among peoples of the world to get trade, social-cultural, science, and technology goals. Moreover, English competence is important in career development, therefore students need to understand and use English to improve their confidence to face global competition. The purpose of teaching writing is to value and improve the skills of writing from the students. The population of this research will be 2014/2015of the eight year students of SMP Al Maksum Stabat. It consist of 30 students, 16 boys and 14 girl. Their age about 14-16 years old. Because the total of the students is less than 100, it is better to take the population as a sample. There are significant differences before and after the students get treatment. For the 30 students, 21 students get the result more than 75 point. It means that 80 percent of the students get more ability in writing after get the treatment. Keywords: writing skill, worksheet